Perlindungan Hukum terhadap guru pesantren terkait kekerasan dan perlakuan tidak adil di Kabupaten Bireuen - Arja, Arin; Sari, Elidar; Ramziati, Ramziati (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
The recent phenomenon is that Islamic boarding school teachers often receive verbal violence from their students' parents and also receive unfair treatment regarding honorariums given from the Ministry of Religion. In fact, it is appropriate for Islamic boarding school teachers to receive legal protection, including protection that arises as a result of the actions of students, student guardians, the community, bureaucracy or other parties. Legal protection for Islamic boarding school teachers is still very general and relatively fragmentary, so that there are many problems, especially in Bireuen Regency, Islamic boarding school teachers in Bireuen Regency have many opinions about unfair treatment, verbal violence from Islamic boarding school teachers and discrimination from the Ministry of Religion. This research aims to study and analyze legal protection for Islamic boarding school teachers in Bireuen Regency, to study and analyze the obstacles that occur to legal protection for Islamic boarding school teachers in Bireuen Regency and to study and analyze the efforts made to prevent obstacles for Islamic boarding school teachers to receive adequate legal protection. both in Bireuen Regency.This research uses empirical juridical methods, and uses a qualitative approach. This research is descriptive in nature, with the research location in Bireuen Regency. Data collection sources consist of primary and secondary data, data collection tools using observation, interviews and documentation, the results of the research are arranged systematically to obtain clarity on the problems to be researched.Based on the results of research that teacher protection for Islamic boarding school teachers in Bireuen Regency is not specifically regulated in the law,. The obstacles that occur to legal protection for Islamic boarding school teachers in Bireuen Regency are the legal substance factor. The Bireuen Regency government does not yet have regional regulations regarding the protection of Islamic boarding school teachers to date so that the protection of Islamic boarding school teachers tends to receive less attention through concrete actions, legal structure factors, enforcement of legal protection against Islamic boarding school teachers in Bireuen Regency have not run well, the legal culture factor in the legal culture aspect is a lack of legal awareness from parents/guardians of students in Bireuen Regency without finding out first regarding the problems that occur. Efforts are being made so that obstacles to legal protection for Islamic boarding schools in Bireuen Regency can be resolved. Socialization and Revision of the Law on Islamic Boarding School Teachers regarding several limitations of the Bireuen Regency government in implementing policies regarding teacher protection. Establishment of the Islamic Boarding School Teacher Protection Agency. Apply for an Operational Permit for the Mujadi Education Unit (SPM).It is recommended that legal protection for Islamic boarding school teachers in the educational process related to acts of violence in the educational sector should be implemented using penal policies and non-penal policies. To anticipate forms of violence that occur in the teaching and learning process, related parties such as school principals, the Education Department and also NGOs working in the education sector should be able to carry out work coordination in trying to stop forms of violence in educational institutions.